THE MILLENNIALS’ EMOTION IN LEARNING USING TECHNOLOGY: DEMONSTRATING RESILIENCE OR FEELING DESPERATION? - Adi Suryani; Soedarso Soedarso (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2021)
The millennial generation is recognized as digital generation. The flourish and fast changing technology and information surround their lives. It is likely to influence and direct how they learn and socialize. One of significant learning media which is popular among today’s generation is video. The use of video, including vlog in English Language Teaching is prevalent today. However, how EFL students feel when they learn and create vlog are still under-examined. Thus, this study aims to explore several EFL students’ emotional experiences when they create vlog and academic video during COVID-19 pandemic outbreak. The study adopts qualitative research method. The data are collected through the students- participants’ narrative and vlog or video analysis. The study reports several findings. The first is the students-participants experience emotional roller coaster of negative and positive states. The second finding is the student-participants develop resilient capacity after regulating emotion by developing self-assurance of personal benefits of learning, creating economic prospect orientation and establishing social senses and global relationship goals. The third finding is it highlights the need to incorporate technology, emotion and cognition learning to fulfil the need and passions of today’s generation.